Reflexões sobre os processos de ensino-aprendizagem de português como língua estrangeira na República Cooperativista da Guiana: desafios e possibilidades - Sousa, Rogério Pinto de (Universidade Federal de São Carlos, 2024)
This paper proposes reflections on the processes of teaching and learning Portuguese as a Foreign Language and an analysis of the use of photography through the social network Instagram as a pedagogical tool in the context of the Co-operative Republic of Guyana, in the city of Lethem. This is a qualitative-interpretivist study, with the methodological proposal of a case study, in which ethnographic data collection techniques are used, involving a volunteer teacher-researcher, students and employees of the Government of Lethem as research participants. As for the theoretical framework, with regard to the teaching and learning of Portuguese as a Foreign Language, authors such as Almeida Filho (1989, 2007), Bardin (1977, 2016), Grimes (2006), García (2009), Piaget (1970), Pozo (1994), among others. This work focuses on the issue of student motivation in the teaching and learning of Portuguese as a foreign language in the Cooperative Republic of Guyana in the city of Lethem and the use of the social network Instagram as a pedagogical tool. The results of analysing the data collected suggest that the Instagram tool can be used as a source of motivation, interaction and a pedagogical tool in PLE classes.
Reflections on theteaching-learning process of portuguese as a foreign language in the Cooperative Republic of Guiana: challenges and possibilities.
Keywords: Motivação; Ensino-aprendizagem; Português como língua estrangeira; Motivation; Teaching and learning; Portuguese as a foreign language; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA